Lugares em cena: caminhos documentários - Helena Augusta da Silva Gomes (2016)
The places, the locations e the scenes: formation conditions of Brazilian documentary films O fim e o princípio, Terra deu, terra come e A falta que me faz. The study is based on reflections about places as fragments of the world and ways to get to see such fragments, through the mediation of images of documentary films and shares and meetings involved in its realization. The instances formed with the contact between alterities the directors and the characters create territories by the encounter between different mise-en-scènes; the film forms are made by spatial proximities, the filmic locations, which are transformed, from the relationships that are established in them, into some new instances. So, rather than search for locations to be filmed, these documentaries seek to establish new places, along with their scenes, made by physical materiality and interpersonal relations, that are built by the proximity of those who share them. The films, made by the convergences of the filmic locations, the places lived by its inhabitants and the relations places shared between the subjects involved in the movies, build new spaces: places in scene.